Osmotic dehydration as an alternative method of food preservation (@limentech, Ciencia y Tecnología Alimentaria, 2019)
Osmotic dehydration is a technique for partial dehydration of foods that consists of immersing them in aqueous solutions of solutes (sugars and/or salts) with high osmotic pressure. The osmotic dehydration process is characterized by two stages: a dynamic stage and an equilibrium stage.In the dynamic stage, matter transfer rates decrease until equilibrium is reached. The osmotic process ends when this equilibrium is reached, i.e. when the net rate of matter transport cancels out. Water is removed mainly by diffusion and capillary flow, while permeation of the feed with solutes and leaching of feed components occur only when the net rate of transport of matter is zero.of feed components occur only by diffusion. In conclusion, the use of osmotic dehydration in the food industry as a pretreatment improves product quality in terms of color, flavor and texture with a minimum energy requirement since it is carried out at low temperatures.
Keywords: Food; dehydration; conservation; osmosis